Comparative study of disability‐free life expectancy across six low‐ and middle‐income countries. Issue 4 (16th May 2016) - Chirinda, Witness; Chen, He
Abstract : Aim: There is a knowledge gap about the disability‐free life expectancy (DFLE) in low‐ and middle‐income countries. The present study aimed to compute and compare DFLE in six such countries, and examine sex differences in DFLE in each country. Methods: Based on data from the World Health Organization Study on Global Aging and Adult Health wave 1 survey, we used the Sullivan method to estimate DFLE among persons aged years 50 years and older. Disability was divided into moderate disability and severe disability during the calculation. Results: Of the six countries, China had the highest DFLE and lowest expected average lifetime with disability. India had the lowest DFLE and highest life years with moderate and severe disability. In each country, women live longer than men, but with more disabilities in both absolute and proportional terms. The huge sex difference in Russia requires special attention. In addition, most of the life expectancy lived with disability was spent with severe disability, rather than moderate disability. Conclusions: The study has shed some light on the disparities across the six countries with regard to DFLE at old ages. The low percentage of DFLE in life expectancy in some countries, such as India, calls for effective policies on healthy aging. The "sex disability‐survival paradox" in DFLE is supported by our results. To differentiate the severity of disability should be routine in calculating DFLE.Geriatr Gerontol Int 2017; 17: 637–644 .